Magnifico - De Los Reyes, Maryo J.; Yamamoto, Michiko; Manio, Jiro; Tolentino, Lorna; MartiI?nez, Albert; Romero, Gloria 1933-; Rodriguez, Celia; Sevilla, Violeta C.; Labad, Lutgardo (Unitel Picture International Distributed by GMA Films, 2003)
When Miong, Magnifico's brother loses his scholarship in Manila, his parents also loses all their hope in having a better life. Added to Miong's failure, there's their youngest sibling Helen who has cerebral palsy and who hasn't spoken yet. It seems fate is playing a prank on them because the grandma, Magda, is also diagnosed to have a terminal illness. Magnifico's sympathetic heart leads him to help his family by planning the burial of his sick grandmother. In fulling his mission, he is bound to influence the lives of his townspeople and change the dim perspective of his family by proving that everything is possible if only one will see through the eyes of a child.